BUILDING RESILIENCE FROM AN EARLY AGE: AN ANALYSIS OF THE FORMS AND FACTORS OF CHILDREN'S ADAPTATION IN THE BATUSANGKAR MARKET ENVIRONMENT - Resti Yulia; Zifnil Afifah; Angraini Daboti; Restu Yuningsih; Meliana Sari; Lany Fitri (Sharia Oikonomia Law Journal, 2026)
This study examines the phenomenon of early childhood adaptation within the complex and dynamic environment of Batusangkar Market. The market environment, with its unique social interactions and emotional stimuli, serves as a distinctive arena for children to develop adaptive capacities. This research contributes to the understanding of how stimulation-rich non-formal environments can shape children's adaptive abilities. The objective is to describe the forms of adaptation and the formative factors of adaptive capacity among early childhood children in the market. This qualitative descriptive case study positions the researcher as the key instrument. Informants, including children active in the market, parents, and traders, were selected through purposive sampling. Data were collected through participant observation, unstructured interviews, and documentation. Data analysis followed the Miles and Huberman model (reduction, display, and verification/conclusion). Data validity was ensured through technical triangulation (observation, interviews, and documentation) and the alignment of findings with reduction tables. The results indicate that early childhood adaptation in the market is formed through the synergy of early habituation, parental education and supervision, modeling, social interaction, and experiential learning. Prominent forms of adaptation include psychosocial and emotional, physical and sensory, behavioral and normative, as well as operational and autonomy. These findings enrich the literature on child developmental psychology, particularly regarding adaptation in dynamic social environments, and offer practical implications for the development of intervention programs. Batusangkar Market is proven effective in fostering independence and adaptive resilience in early childhood.